Changing livelihood options as adaptation: A comparative analysis of three flood control schemes in the Vietnamese Mekong Delta - Tran Anh Thong (2019)
Population, Development, and the Environment - Challenges to Achieving the Sustainable Development Goals in the Asia Pacific